Ethics for the junior officer selected cases from current military experience - Montor, Karel; Mostert, Justin R. (Naval Institute Press, 2001)
Originally compiled and edited by the late Karel Montor, a longtime professor of leadership at the U.S. Naval Academy, with a foreword by VADM James B. Stockdale, USN, Ret., and now fully updated by a team from the Center for the Study of Professional Military Ethics at the Naval Academy, this volume contains over one hundred case studies from and about active-duty U.S. military officers facing ethical challenges on the job. In a short narrative, each case describes the ethical challenge faced by a junior officer. It then asks readers what they think is the right thing to do in that situation. This valuable hands-on reference also includes discussion questions and an analysis of each case study.